Facile synthesis of poly[1‐p (tolylsulfonyl) pyrrole] via Ce (IV)‐pyrrole redox initiating system and polyacrylonitrile blended nanofibers - Ismar, Ezgi; Sarac, A. Sezai (Wiley, 2018)
Chemical polymerization of monomers of electroactive polymers and their processability have some challenges. Chemical polymerization of 1‐p‐(tolylsulfonyl) pyrrole has been realized first time by using Ce (IV)‐pyrrole redox initiating system to obtain poly (1‐p‐[tolylsulfonyl)pyrrole]. Moreover, the achieved polymer was used as a precursor for electrospinning, and their solutions with DMF were used to fabricate nano and submicron fibers via electrospinning method. Polymerization conditions were followed with UV–visible spectroscopy. Surface morphologies were examined with scanning electron microscopy, and elemental analysis measurements were obtained via scanning electron microscopy/energy‐dispersive X‐ray. Attenuated total reflection spectroscopy was used to record the characteristic peaks of the nanofiber webs before and after polymerization. Surface morphology of the polymer domains was examined with atomic force microscopy. Inherently conductive polymer, poly (1‐p‐[tolylsulfonyl)pyrrole] was successfully combined with the PAN and were fabricated to obtain nanofiber webs.